Comparative Analysis of Electoral Technology Deployment and Voter Trust in the 2015, 2019, and 2023 General Elections in Nigeria - Abdulrahman, Abubakar (Kashere Journal of Politics and International Relations, 2025)
The integrity of electoral processes is fundamental to democratic consolidation, and technological innovations have increasingly been adopted to enhance transparency and credibility. This study conducts a comparative analysis of electoral technology deployment and voter trust in Nigeria’s 2015, 2019, and 2023 general elections. Drawing on a mixed-methods approach that includes document analysis, public opinion surveys, and key informant interviews, the study evaluates the evolution and effectiveness of technologies such as the Smart Card Reader (SCR), the Bimodal Voter Accreditation System (BVAS), and the electronic transmission of results. Findings reveal that while the 2015 elections marked a turning point with the introduction of SCR, subsequent elections in 2019 and especially 2023 saw significant technological upgrades intended to address past deficiencies. However, the study also finds that technological deployment alone does not guarantee voter trust; factors such as operational reliability, INEC’s transparency, political interference, and public awareness significantly shape electoral credibility. The 2023 elections, despite the introduction of BVAS and result upload portals, witnessed mixed reactions from the electorate due to perceived inconsistencies and logistical shortcomings. The study concludes that while electoral technology has the potential to enhance voter trust, its impact is contingent upon effective implementation, stakeholder confidence, and institutional accountability. Recommendations are offered to strengthen the integration of technology in Nigeria’s electoral process for future democratic resilience.